1999
DOI: 10.1136/fn.80.1.f15
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of elective high frequency ventilation in preterm infants with respiratory distress syndrome

Abstract: Aim-To summarise the evidence on the eYcacy of elective high frequency ventilation compared with conventional ventilation in preterm infants with respiratory distress syndrome. Methods-A search from 1987 onwards was made on Embase, Medline, and the Cochrane Library. A questionnaire was also circulated during an international meeting on high frequency ventilation. To be included in the data synthesis, studies had to be randomised controlled trials comparing elective high frequency ventilation with conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…34 Potentially, a lower Paco 2 may reduce the risk of IVH by causing arterial vasoconstriction. However, low Paco 2 has been described as a risk factor for periventricular leukomalacia and a poor neurologic prognosis, 19 so there is a need for caution in interpreting this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Potentially, a lower Paco 2 may reduce the risk of IVH by causing arterial vasoconstriction. However, low Paco 2 has been described as a risk factor for periventricular leukomalacia and a poor neurologic prognosis, 19 so there is a need for caution in interpreting this finding.…”
Section: Discussionmentioning
confidence: 99%
“…19 Pregnancy-induced hypertension is associated with a lower rate of IVH. 5,20 For reducing the incidence of IVH, several pharmacological interventions have been proposed, including antenatal steroids, 5,8,10,15,21,22 prenatal tocolytic therapy, 8,23 postnatal administration of low-dose indomethacin, 24,25 and surfactant.…”
mentioning
confidence: 99%
“…HFOV reduced the incidence of CLD at 36 weeks in 2 studies [9,13], in contrast with other trials including our own [2,10,11]. A meta-analysis of the studies using HVS based on the results of the 2 studies discussed above [9,13] concluded that HFOV reduced the incidence of CLD at 36 weeks [18].…”
Section: Clinical Trialsmentioning
confidence: 59%
“…E ditor —Cools and Offringa’s recent meta-analysis of elective high frequency ventilation (HFV) in preterm infants with respiratory distress syndrome1 concludes that HFV reduces the risk of chronic lung disease (CLD) at 36 weeks of postconceptional age, but may be associated with an increased risk of severe intraventricular bleeding. Several areas of uncertainty remain, however, and they suggest that new clinical trials should be done in very preterm infants to evaluate the usefulness of elective HFV, using a high lung volume strategy, started as soon as possible after birth.…”
mentioning
confidence: 99%